Determinants of industrial embeddedness: Evidence from African manufacturing firms - Abdelrasaq Na-Allah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Recent developments in policy initiatives as well as some current practical events have combined to put the spotlight on the issue of industrial embeddedness in sub-Saharan Africa. Though extant research documents, some stylized facts, as determinants of its manifestations of their relevance to realities in the sub-continent, have until now been overlooked. Yet, it is difficult to ignore the fact that its constituent economies possess some peculiar attributes with potentially significant implications for embeddedness behaviour. Using data for the country of Lesotho, a probit model is estimated to ascertain the veracity of some of the widely acclaimed explanatory factors. We find, as we argue, that among all, the issue of supply potentials appears the most important.
Keywords: L60; F23; O25; O55; 330; industrial embeddedness; supplier linkages; manufacturing; probit model; sub-Saharan Africa